2015
DOI: 10.1038/pr.2015.261
|View full text |Cite
|
Sign up to set email alerts
|

The viral dsRNA analogue poly (I:C) induces necrotizing enterocolitis in neonatal mice

Abstract: Background: Necrotizing enterocolitis (NEC) is a lifethreatening gastrointestinal disease in premature infants with high mortality and morbidity with uncertain pathogenesis. Recent research focused on the role of intraluminal bacteria and lipopolysaccharide (LPS). However, an additional role of viral agents in the pathogenesis of NEC has recently been postulated. We assessed the role of polyinosinic:polycytidylic acid (pIC) mimicking viral dsRNA in contributing to the development of NEC in neonatal mice. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The remaining intestinal tissue was fixed for three days in 10% buffered paraformaldehyde (PFA) and embedded in paraffin, sectioned (4 μm) and stained with hematoxylin-eosin using a standard protocol. Small and large intestinal tissue was investigated histologically for intestinal damage as previously described [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining intestinal tissue was fixed for three days in 10% buffered paraformaldehyde (PFA) and embedded in paraffin, sectioned (4 μm) and stained with hematoxylin-eosin using a standard protocol. Small and large intestinal tissue was investigated histologically for intestinal damage as previously described [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Animals were randomly divided into two groups (i) LPS: Formula feeding supplemented with LPS from E . coli 0127:B8 (10μg/g body weight, Sigma Aldrich) and exposure to hypothermia and hypoxia as previously described [ 11 ]; (ii) DSS: Formula feeding supplemented with 3% (w/v) DSS without physical stress. Age-matched breast fed animals served as controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Necrosis of the intestinal tract significantly compromises the function of the digestive system and results in a loss of appetite and weight loss (4). Additionally, previous studies have indicated that inflammation and apoptosis are associated with disease progression in patients with neonatal NEC (5,6). Therefore, attenuating inflammation and inhibiting the apoptosis of epithelial cells in the small intestine are potential methods of treating neonatal NEC.…”
Section: Introductionmentioning
confidence: 99%